INFLUENCE OF BOARD OF MANAGEMENT’S MOTIVATIONAL STRATEGIES ON KCPE PERFORMANCE IN PUBLIC PRIMARY SCHOOLS OF MIGORI SUB COUNTY IN MIGORI COUNTY, KENYA - Opande, Maurice Ojanga; Kathuri, Prof. Nephat J.; Bahati, Sabina Mureithi (IJRDO - Journal of Applied Management Science, 2017)
Management is the process of acquiring and utilizing resources in order to achieve organizational goals. It is a process that can be taken by an individual or individuals to coordinate the activities of others in order to achieve set organizational goals. This study was aimed at investigating the influence of Board of Management’s motivational strategies on KCPE performance in public primary schools of Migori Sub County, Migori Count. Results showed that the level of supervision, recognition, working environment and rewarding teachers/learners determined learners’ performance in KCPE.